Organizational and Methodological Approach to the Description and Standardization of Treatment and Diagnostic Processes in a Multidisciplinary Hospital - A. Y. Perminov; N. S. Fomenko; S. S. Petrikov; F. M. Navzadi (Неотложная медицинская помощь, 2021)
Today, there is a tendency to shift the focus of management from structural units to treatment and diagnostic processes in Russian healthcare institutions. To organize effective management of the treatment and diagnostic process, it is necessary to have its formalized description. This article presents the main results of a study conducted on the basis of N.V. Sklifosovsky Research Institute for Emergency Medicine, which was aimed at the development of an organizational and methodological approach to the description and standardization of treatment and diagnostic processes, taking into account the specifics of the activities of a multidisciplinary medical hospital.When developing the organizational and methodological approach, the  methods of system analysis and modeling, factual data on the structure and  parameters of the treatment and diagnostic processes of the hospital, as well as the experience and expert opinions of the Institute staff were used. In the course of the study, the analysis of the organizational and economic  characteristics of the treatment and diagnostic processes was carried out and the requirements for the format of their description and the introduction of the notation into the practice of the hospital were formulated. Taking into account these requirements, the authors have developed and presented the format of the modified operogramme, which combines the ability to reflect both the logic of the process and the interaction of its participants, and the resource characteristics of the actions of the process. The article presents an organizational and methodological approach to the description and standardization of treatment and diagnostic processes, developed and tested by the authors, based on modified operogrammes and tables of summary resource characteristics.The organizational part of the approach is based on the principle of maximum involvement of medical personnel of various categories in the description and standardization of processes through the formation of small groups, as well as on a system of multi-level examination of the developed models, checking them on statistical data to confirm the adequacy of expert assessments.In N.V. Sklifosovsky Research Institute for Emergency Medicine 15 small  groups work on the main profiles of medical and diagnostic care on a  regular basis, more than 150 doctors are involved in the description and standardization, 232 models of complex medical and diagnostic processes, surgical interventions, active methods of treatment and diagnostics have been developed.The operogrammes and summary tables of resource characteristics prepared using the above-described organizational and methodological approach, agreed within the hospital, become the basis for solving various organizational and economic tasks, including the development of internal recommendations, checklists, calculation of standard cost, resource planning, etc.